Pendampingan Pelatihan Instruktur Senam Bagi Siswa Sekolah Dasar Di Nagari Padang Magek (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
Gymnastics is physical exercise that is deliberately and planned, arranged systematically to shape and develop the body in harmony. This activity has become a popular sport among the public. Maintaining physical health is very important for the entire community, therefore we carry out a real work program, namely training assistance for gymnastics instructors.  The aim of the gymnastics instructor training assistance activity every Sunday morning which is held by PLB students at Jorong Guguak Gadang Nagari Padang Magek every Sunday morning, is so that children can become gymnastics instructors at their school. This research method uses a Participatory Action Research (PAR) approach, the research involves the participation of children and PLB students. The conclusion from the results of this service is the implementation of gymnastics instructor training and the achievement of mastery and teaching of gymnastics for children in Padang Magek.